Paralysis caused by dinotefuran at environmental concentration via interfering the Ca2+–ROS–mitochondria pathway in Chironomus kiiensis - Wei, Fenghua; Gu, Weiwen; Zhang, Fengru; Wu, Shuangxin (Frontiers in Public Health, 2024)
Introduction Dinotefuran as the third-generation of neonicotinoid insecticides is extensively used in agriculture worldwide, posing a potential toxic threat to non-target animals and humans. However, the chronic toxicity mechanism related to mitochondria damage of dinotefuran to non-target animals at environmental concentration is unclear. Methods In this study, the mitochondria damage and oxidative stress of dinotefuran on Chironomus kiiensis were investigated at environmental concentrations by long-term exposure. At the same time, relevant gene expressions of these toxicity indexes were measured as sensitive ecotoxicity biomarkers to reflect the toxic effects of dinotefuran on Chironomidae. Results Our present study showed that chronic exposure to environmental concentrations of dinotefuran resulted in behavioral inhibition in the larvae of Chironomidae. For burrowing inhibition of 10 days, the lowest observed-effect concentration (LOEC) and 50% inhibitory concentration (IC50) were 0.01 (0.01–0.04) and 0.60 (0.44–0.82) μg/L, respectively. Dinotefuran promoted the release of intracellular calcium ions (Ca2+) in Chironomidae via dysregulating the gene expressions of atp2b, camk ii, and calm. Subsequently, the disruption of the Ca2+ signaling pathway induced oxidative stress by raising reactive oxygen species (ROS), hydrogen peroxide (H2O2), and malonaldehyde (MDA) levels. Thus, the over-release of Ca2+ and ROS disordered the normal functioning of mitochondrial-related pathways by dysregulating the expressions of mitochondria-related genes of atpef0a, sdha, and cyt b. Conclusion Our findings showed that low environmental concentrations of dinotefuran caused paralysis of the midge via interfering the Ca2+–ROS–mitochondria pathway. These results provided data support for assessing the potential environmental risk of dinotefuran.